2007
DOI: 10.1515/epoly.2007.7.1.1744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and pH on swelling behavior of hydroxyethyl cellullose-acrylamide hydrogel

Abstract: The swelling behavior of hydroxyethyl cellulose-acrylamide hydrogels at different pH and temperatures was studied. The absorption increased for the first 12 hours and then decreased. Several hydroxyethyl cellulose-acrylamide ratios were studied. Increasing hydroxyethyl cellulose amount decreased swelling, indicating that swelling was affected by increase in crosslinking. Three different levels of crosslinking agent were studied. Hydrogels exhibited a thermal and pH sensitive behaviour. Highest swelling capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…10, the swelling behaviour of the poly (acrylamide-co-acrylic acid) potassium salt and sodium acrylate typically demonstrate maximum swelling between pH 6.5 (neutral medium) and 9 after free swelling at 25 °C for 2-, 4-and 6-h. This observation is in agreement with Lenji et al [25] and Alonso et al [21] who also observe that the optimal range for the hydrogels was at a temperature of about 30 °C, between pH 7 and 9. Figure 10a-c reflects the transient behaviour of the SPHs, with the highest swelling performance being observed at pH 9 after 2 h of free swelling.…”
Section: Effect Of Phsupporting
confidence: 92%
See 2 more Smart Citations
“…10, the swelling behaviour of the poly (acrylamide-co-acrylic acid) potassium salt and sodium acrylate typically demonstrate maximum swelling between pH 6.5 (neutral medium) and 9 after free swelling at 25 °C for 2-, 4-and 6-h. This observation is in agreement with Lenji et al [25] and Alonso et al [21] who also observe that the optimal range for the hydrogels was at a temperature of about 30 °C, between pH 7 and 9. Figure 10a-c reflects the transient behaviour of the SPHs, with the highest swelling performance being observed at pH 9 after 2 h of free swelling.…”
Section: Effect Of Phsupporting
confidence: 92%
“…Different investigators have reported the optimal temperatures for different hydrogel samples tested. For example, Singh and Dhaliwal [18] have reported 50 °C and Alonso et al [21] have reported 30 °C; the optimal temperature range of the hydrogels in this study was evaluated to be between 50 and 75 °C.…”
Section: Effect Of Temperaturementioning
confidence: 96%
See 1 more Smart Citation
“…The synthesis of HEC/PAAm has been previously studied by Alonso et al [7], by means of free radicals using potassium persulfate (KPS), demonstrating the dependence of pH and temperature on the swelling of gels. The gels showed a maximum swelling of 1200 wt%, at a temperature of 30°C, decreasing when the temperature and amount of HEC in the gel matrix increased.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling and deswelling behaviors of scaffolds in aqueous are essential in biomedical applications because they control the diffusion and release of drugs and nutrients in tissue application [23]. The high swelling and deswelling rate of MWCNT-agarose scaffolds might be ascribed to the hydrophilicity nature of both agarose and water dispersed MWCNTs or/and changes of agarose scaffolds in spatial structure caused by MWCNTs [10,22,70]. As the concentration of MWCNT increases, the swelling and deswelling rate of scaffolds reduce may be attributed to the decrease of free space among agarose chains.…”
mentioning
confidence: 99%